OPTN/SRTR 2015 Annual Data Report: Lung. (January 2017) - Valapour, M.; Skeans, M. A.; Smith, J. M.; Edwards, L. B.; Cherikh, W. S.; Uccellini, K.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: In 2015, 2409 active candidates aged 12 years or older were added to the lung transplant waiting list; 2072 transplants were performed, the most of any year. The median waiting time for candidates listed in 2015 was 3.4 months; the shortest waiting time was for diagnosis group D. Despite the highest recorded transplant rate of 157 per 100 waitlist years, waitlist mortality continued a steady decade‐long rise to a high of 16.5 deaths per 100 waitlist years. Measures of short‐ and long‐term survival showed no trend toward improved overall survival in the past 5 years, except that 6‐month death rates decreased from 9.4% in 2005 to 7.9% in 2014. At 5 years posttransplant, 55.5% of recipients remained alive. In 2015, 23 new child (ages 0–11 years) candidates were added to the list; 17 transplants were performed. Incidence of death was 6.1% at 6 months and 8.2% at 1 year for transplants in 2013–2014. Important policy changes will affect access to transplant. In February 2015, OPTN implemented a comprehensive revision of the lung allocation score to better reflect mortality risk. Broader geographic sharing of donor lungs for pediatric candidates and allowance for selected transplants across blood types for candidates aged younger than 2 years have been approved and are expected to improve pediatric access to transplant. The impact of these changes on lung transplant trends will be observed in the coming years.